2018
DOI: 10.1016/j.clinimag.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Visibility of mammographically occult breast cancer on diffusion-weighted MRI versus ultrasound

Abstract: DWI may detect more mammographically occult cancers than ultrasound, warranting further investigation as an alternative supplemental screening technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…In a study involving 118 mammographically occult lesions (91 benign, 27 malignant), DW MRI could detect 89% of the DCE MRI-detected malignancies, when the readers were not blinded to the images from DCE MRI (56). In another nonblinded study involving 60 mammographically occult cancers, DW MRI detected more cancers, compared to the MRI-guided focused ultrasound (78% and 63%, respectively, p = 0.049) (77). In previous blinded reader studies in which the readers assessed only unenhanced MRI sequences, including DW MRI with or without nonenhanced T1/T2weighted image, the sensitivity of DW MRI in various study designs ranged from 45% to 94% (27,34,49,50,78,79).…”
Section: Unenhanced Mri For Breast Cancer Screeningmentioning
confidence: 96%
“…In a study involving 118 mammographically occult lesions (91 benign, 27 malignant), DW MRI could detect 89% of the DCE MRI-detected malignancies, when the readers were not blinded to the images from DCE MRI (56). In another nonblinded study involving 60 mammographically occult cancers, DW MRI detected more cancers, compared to the MRI-guided focused ultrasound (78% and 63%, respectively, p = 0.049) (77). In previous blinded reader studies in which the readers assessed only unenhanced MRI sequences, including DW MRI with or without nonenhanced T1/T2weighted image, the sensitivity of DW MRI in various study designs ranged from 45% to 94% (27,34,49,50,78,79).…”
Section: Unenhanced Mri For Breast Cancer Screeningmentioning
confidence: 96%
“…Greater visibility of mammographically occult breast cancer on DWI compared to ultrasound was shown by Amornsiripanitch et al. ( 14 ). Compared to DCE-MRI, Pinker et al.…”
Section: Clinical Applicationsmentioning
confidence: 83%
“…Superior performance of DWI in the evaluation of mammographically occult and non-palpable breast cancers, particularly in women with dense breasts, compared to mammography alone has been reported (12,13). Greater visibility of mammographically occult breast cancer on DWI compared to ultrasound was shown by Amornsiripanitch et al (14). Compared to DCE-MRI, Pinker et al showed that current DWI as a standalone tool demonstrates inferior sensitivity and diagnostic performance (15).…”
Section: Clinical Applications Screeningmentioning
confidence: 99%
“…The literature suggests that lesions with sizes less than 1 cm and DCIS manifesting as calcifications may be more difficult to detect on DW MRI [ 16 23 24 25 30 ]. The lower detection rate for smaller cancers (≤ 0.5 cm) in our study was expected, given that our DW MRI axial in-plane spatial resolution (1.9 × 1.9 mm 2 ) and section thickness (3 mm) could result in a partial volume effect for small lesions.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that DW MRI can be part of a multiparametric or non-contrast-enhanced approach for local staging of the affected breast in women with breast cancer [ 21 22 ]. In detecting clinically occult breast cancer, the sensitivity of DW MRI is lower than that of DCE MRI, but probably higher than that of mammography or targeted US [ 23 24 25 26 ]. However, the performance of DW MRI, relative to that of combined mammography and whole-breast US, in the detection of clinically occult breast cancer is unknown [ 16 ].…”
Section: Introductionmentioning
confidence: 99%